Effects of antimony content in MgAg0.97Sbx on output power and energy conversion efficiency. (1st January 2016) - Liu, Zihang; Shuai, Jing; Mao, Jun; Wang, Yumei; Wang, Zhengyun; Cai, Wei; Sui, Jiehe; Ren, Zhifeng
Abstract: We report the effect of Sb content in MgAg0.97 Sbx (x = 0.99, 0.9925, 0.995, and 1.00) on output power and leg efficiency. Due to the doubling of carrier concentration with increasing the Sb content, power factor is enhanced around 20% over the whole temperature range. Simultaneously, the average thermoelectric figure of merit ( ZT ) is even enhanced a little in spite of the increased corresponding thermal conductivity. We further calculated the engineering power factor (PF) eng, output power, engineering figure of merit (ZT) eng and leg efficiency by taking into account of the Thomson effect. Assuming T c = 300 K and T h = 548 K, leg length ∼2 mm, an output power of ∼1.77 W cm −2 and leg efficiency η of ∼10.1% are finally obtained for the optimized composition MgAg0.97 Sb0.995 . Graphical abstract: Large enhancement of output power coupled with high leg efficiency could be successfully achieved via finely tuning the Sb content for MgAg0.97 Sbx (x = 0.99, 0.9925, 0.995, and 1.00).